Exploring the potential of solar power for residential use in Malaysia: Insights from solar companies and local authorities - Goh, Kai Chen; Kong, Jia Wen; Chai, Changsaar; Lee, Chia Kuang (Malaysian Institute of Planners, 2024)
With extremely strong solar radiation during the year, Malaysia has the greatest potential for solar-energy implementation. However, despite the widespread interest in the country, solar energy is still not widely utilized in residential buildings. Thus, this research aimed to identify the implementation and challenges of implementing solar energy in residential buildings and strategies to promote solar energy in Malaysia. Thirteen responses from representatives of solar companies in Malaysia were obtained through interviews. Through the research results, the implementation and challenges faced in implementing solar technologies were identified, together with strategies to promote solar technology. High installation costs, lack of awareness, and lack of incentive schemes are the barriers that prevent people from installing solar technology, as revealed by the interviews. Therefore, the government should make greater efforts to promote solar energy to the public. Interviewees suggested successful financial incentive schemes, personal tax exemptions, and public awareness programs to attract consumer interest as ways to increase solar adoption. The findings of this research may be used to help the government develop policies to promote solar energy for electricity consumption in residential buildings.